2020
DOI: 10.3390/metabo10120495
|View full text |Cite
|
Sign up to set email alerts
|

Single-Step Extraction Coupled with Targeted HILIC-MS/MS Approach for Comprehensive Analysis of Human Plasma Lipidome and Polar Metabolome

Abstract: Expanding metabolome coverage to include complex lipids and polar metabolites is essential in the generation of well-founded hypotheses in biological assays. Traditionally, lipid extraction is performed by liquid-liquid extraction using either methyl-tert-butyl ether (MTBE) or chloroform, and polar metabolite extraction using methanol. Here, we evaluated the performance of single-step sample preparation methods for simultaneous extraction of the complex lipidome and polar metabolome from human plasma. The meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
40
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(41 citation statements)
references
References 47 publications
1
40
0
Order By: Relevance
“…A major challenge in lipidomics experiments have been the high variability in the signals and even the "shared reference materials harmonize lipidomics across MS-based detection platforms and laboratories" have shown that most lipid species showed large variability (CV) between 30% to 80% 48 . However variability for endogenous lipid species that were normalized to the corresponding stable isotope-labelled analogue were lower than 30% 43,48 . In this method, we used sum normalization (although we are not addressing batch effect in this study) and found that 849 lipid species had a CV <30% 43 .…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…A major challenge in lipidomics experiments have been the high variability in the signals and even the "shared reference materials harmonize lipidomics across MS-based detection platforms and laboratories" have shown that most lipid species showed large variability (CV) between 30% to 80% 48 . However variability for endogenous lipid species that were normalized to the corresponding stable isotope-labelled analogue were lower than 30% 43,48 . In this method, we used sum normalization (although we are not addressing batch effect in this study) and found that 849 lipid species had a CV <30% 43 .…”
Section: Discussionmentioning
confidence: 87%
“…We report a single extraction, targeted mass spectrometric method using Amide-HILIC-chromatography and scheduled MRM with variable-RTW and relative-DTW which detects more than 1000 lipid species from 18 lipid classes including various isomers in a single run of 24 minutes. With this method, which covers most of the lipid species which are present in human plasma with 14-22 carbons atoms and 0-6 double bonds in fatty acid chain, we could identify considerably higher number of lipid species than those reported in previous large-scale lipidomics studies 14,21,4345 .…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…When applying the equation to all 81 authentic standards, an R 2 value of 0.87 was achieved (Figure S3C). Equation shows the conversion formula, which had equal performance whether it was trained on our subset of 10 authentic standards or the full set of 81. As a second independent validation of our approach, we used optimized MRM data from an Agilent 6495 QqQ that was included in a study by Medina et al We determined that the majority of optimal product ions found by the Agilent 6495 QqQ were also among the five most abundant fragments in the Orbitrap ID-X MS2 data (Figure S4A). As expected, we were able to improve our ability to accurately predict optimal Agilent 6495 CE values from Orbitrap ID-X data by using the conversion formula derived from the analysis of the 10 authentic metabolites listed above (Figure S4B,C).…”
Section: Resultsmentioning
confidence: 99%
“…In a recent study, extraction methods that yield hydrophilic and lipophilic layers have been applied, and a simultaneous extraction procedure for the profiling of polar and mid-polar metabolites has also been reported. Medina et al recommended that a mixture of isopropanol and 1-butanol:methanol worked best for the analysis of lipids and polar metabolites from human plasma [ 78 , 79 ]. Therefore, it is imperative to apply a customized extraction method that considers the polarity of the metabolites of interest.…”
Section: Metabolomics Workflowmentioning
confidence: 99%